2012
DOI: 10.1128/mcb.00212-12
|View full text |Cite
|
Sign up to set email alerts
|

Sos7, an Essential Component of the Conserved Schizosaccharomyces pombe Ndc80-MIND-Spc7 Complex, Identifies a New Family of Fungal Kinetochore Proteins

Abstract: Chromosome segregation is powered by the kinetochore, a large macromolecular structure assembled on centromeric chromatin. Attachment of sister chromatids to microtubules is mediated by the highly conserved tripartite KMN (acronym for KNL-1-Mis12-Ndc80) kinetochore network. In the fission yeast Schizosaccharomyces pombe, the equivalent complex is called NMS (Ndc80-MIND-Spc7). Here, we show that not all components of the NMS complex had been identified previously. A 10th NMS component exists, the essential Sos7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…For example, it has been reported that strains expressing nmt81::GFP-Atb2 at the atb2 Ï© locus have altered MT properties (24,(27)(28)(29). The reason for this is unclear.…”
Section: Asp1mentioning
confidence: 99%
“…For example, it has been reported that strains expressing nmt81::GFP-Atb2 at the atb2 Ï© locus have altered MT properties (24,(27)(28)(29). The reason for this is unclear.…”
Section: Asp1mentioning
confidence: 99%
“…It has been proposed that this phosphorylation is required for recruitment of the RZZ complex and the dynein motor to kinetochores, which in turn is important for chromosome motility and SAC signaling (Famulski and Chan, 2007;Kasuboski et al, 2011). Very recently, a potential functional homologue of ZWINT has been identified in fission yeast as a binding partner for the yeast KNL1 homologue Spc105 (Jakopec et al, 2012).…”
Section: Knl1mentioning
confidence: 99%
“…The double‐headed arrows indicate mutual dependency between proteins and protein complexes. The interdependence of various KT proteins shown here is based on the data assembled from the literature – for the S. cerevisiae KT (Meluh & Koshland, ; Ortiz et al ., ; Russell et al ., ; Goshima & Yanagida, ; He et al ., ; Janke et al ., , ; Li et al ., ; De Wulf et al ., ; Nekrasov et al ., ; Pinsky et al ., ; Scharfenberger et al ., ; Westermann et al ., ; Collins et al ., ; Camahort et al ., ; Mizuguchi et al ., ; Pagliuca et al ., ; Schleiffer et al ., ; Bock et al ., ; Nishino et al ., ), for the S. pombe KT (Takahashi et al ., ; Chen et al ., ; Hayashi et al ., ; Liu et al ., ; Saitoh et al ., ; Sanchez‐Perez et al ., ; Kerres et al ., , ; Dunleavy et al ., ; Takayama et al ., ; Pidoux et al ., ; Tanaka et al ., ; Williams et al ., ; Jakopec et al ., ) and for the C. albicans KT (Burrack et al ., ; Roy et al ., ; Thakur & Sanyal, , ).…”
Section: Discussionmentioning
confidence: 99%
“…a). Clustered KTs are found in S. pombe as well except at metaphase where multiple foci of KT proteins were observed (Goshima et al ., ; Tanaka et al ., ; Jakopec et al ., ). Although the exact nature of KT architecture in yeasts is uncertain, various genetic and biochemical studies indicate the presence of functional homologs of several KT proteins at distinct layers of a human KT in these yeasts (Table ).…”
Section: The Kinetochore Structurementioning
confidence: 99%
See 1 more Smart Citation